PERBEDAAN KADAR KOLESTEROL TOTAL DARAH PADA PEKERJA KANTORAN DAN PEKERJA KASAR - Ni Kadek Dwi Rara Santi; Putu Ayu Parwati; Ni Ketut Ayu Mirayanti (Politeknik Medica Farma Husada Mataram, 2019)
Cholesterol is a factor that influences cases of coronary heart disease. One of the factors that influence blood cholesterol is physical activity. Each type of occupation has different physical activities and will affect blood cholesterol. In the group of office workers, less physical activity and more dominant work just sit and cause an increase in blood cholesterol levels. For groups of menial workers, more physical activity is carried out so that blood cholesterol levels can be controlled. This study aims to determine differences in total blood cholesterol levels between office workers and menial workers in Sukawati Gianyar. This type of research is analytic with cross sectional approach. Samples were 30 office workers and 30 menial workers. The results showed the mean total cholesterol level of office workers blood was 194.40 ± 30.56 mg / dL and menial workers were 158.63 ± 35.28 mg / dL. Based on the results of the Independent Sample T-Test, p value of 0.000 is obtained where p <0.05 which means there are differences in blood cholesterol levels in office workers and menial workers. The results showed the average level of total cholesterol in office workers was higher than in menial workers. This is due to lack of physical activity every day in office workers. Suggestions in this study are expected to further researchers can examine the lipid profile of office workers and menial workers.